Catalytic Hydrogenation for Bio‐Oil Upgrading by a Supported NiMoB Amorphous Alloy. Issue 12 (21st October 2013) - Zhang, M. J.; Li, W. Z.; Zu, S.; Huo, W.; Zhu, X. F.; Wang, Z. Y.
Abstract A method of ultrasound‐assisted reduction of a nickel‐ammonia complex with borohydride in aqueous solution was used to prepare NiMoB/MCM‐41 and NiMoB/SBA‐15 supported amorphous alloy catalysts. These catalysts were used to upgrade bio‐oil at mild temperatures ranging from 100 to 160 °C and recycling of these two supported catalysts and of unsupported NiMoB was carried out. Then, fresh and third time used catalysts were characterized by X‐ray diffraction, X‐ray photoelectron spectra, and transmission electron microscopy. Quantitative results were obtained from the analysis of gas chromatography/mass spectrometry. Through mild upgrading, 1‐hydroxy‐2‐propanone, furfural, and 2‐methoxy‐4‐vinylphenol in the bio‐oil were converted to relevant alcohols and saturated phenols. The conversion rates were 45.7, 71.5, and 57.1 %, respectively, when crude bio‐oil was upgraded using NiMoB/MCM‐41 at 160 °C. The two supported catalysts, especially NiMoB/MCM‐41, had smaller amorphous NiMoB particles and exhibited more uniform dispersion on mesoporous silica, leading to higher reaction activity and stability than unsupported NiMoB. Deactivation of these catalysts resulted from the reduction of Ni0, B0, and Mo4+ species on the surface, the transition from the amorphous to the crystalline state, particle agglomeration, and coke deposition on the surface.